Enhanced SPR Response Using Au/GO Thin Films Via Kretschmann Coupling By Controlling The Incident Light Intensities - Noor Faezah Murat; Wan Maisarah Mukhtar; P. Susthitha Menon (INOE Publishing House, 2024)
Non-Indexed Publication